The correlation between hope with acceptance of parents toward children with special needs in the special education school in all districts of Ngawi - Hana Anjasari; Erma Kumala Sari; Priyono Priyono (JPK (Jurnal Pendidikan Khusus), 2020)
This research aims to determine the relationship between hope and acceptance of parents toward children with special needs in special education school in all district of Ngawi. This research’s design used quantitative, with correlational research types. The subject in this research were parents of children with special needs who are at junior high and senior high special school levels, amounting to 52 people. Determination of subject used purposive sampling technique. The data collection technique used two attitude scale, namely parents hope scale (α=0,873) and parents acceptance scale (α=0,877). Data analysis used product moment correlation between Pearson. The result of correlation test showed a correlation coefficient value of 0,688 with value rtabel of 0,279, so rhit rtabel (ρ0,05) for a significance level of 5%. The result of correlation test is that there was a positive significant relationship between hope and acceptance of parents toward children with special needs who are at junior high and senior high special school levels in special education school in all districts of Ngawi.